HARD RESEARCH ON A SOFT SUBJECT: HYPOTHESIS-TESTING IN ECONOMIC EDUCATION. - Fels, Rendigs (Southern Economic Journal)
Focuses on the research in economic education in the U.S. Measurement of economic knowledge; Realm of hypothesis testing in economic education; Inclusion of economic policy in elementary economic education.